The Relationship between Knowledge and Attitudes of Postpartum Mothers regarding Vulva Hygiene and Prevention of Perineal Wound Infections at the Sulastri Clinic - Nurmaliza, Lili; Lubis, Rhina Chairani; Muryani, Muryani (International Journal of Public Health Excellence (IJPHE), 2023)
Perineal tearing that occurs when mothers are in the postpartum phase during the birthing process increases every year and wound healing also takes a long time. This of course occurs due to several factors, one of which is vulva hygiene. According to a survey at the Sulastri Clinic in 2023, out of 10 postpartum mothers, around 7 patients had injuries lasting more than 7 days. This is because mothers who are in the postpartum phase do not practice good vulva hygiene because they are afraid of touching the stitched wound and are also afraid of experiencing a long recovery. The research method used was quantitative and cohort methods. The population of postpartum mothers at the Sulastri Clinic in 2023 will be around 35 postpartum mothers. The sampling method prioritizes the concept of Consecutive Sampling. Then for the independent variable vulva hygiene and also the dependent variable or bound to the speed of healing of perineal wounds in postpartum mothers. Research data was obtained using questionnaires and also observation. The data was tabulated and also analyzed using Fisher's Exact Test. The results of the study show that p = 0.000, α = 0.05 p < α where H1 will be accepted due to the correlation between vulva hygiene and rapid healing of perineal wounds in postpartum mothers. It is hoped that this research can increase the role of health workers in healing perineal wounds in postpartum mothers.